The Study on Value of Recreational Sports Activity of Urban Communities - Hanani, Endang Sri (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2017)
According to the WHO, health is not merely the absence of disease or infirmity, but a state of complete physical, mental, and social well-being. Recreational sports activities particularly for urban communities could be used as a life style, because it may considered balance individual condition between physical, spiritual and social needs. This study aims to describe and investigate: 1) the reason why recreational sports become urban society choice as weekend activities and holiday activities, 2) the type of recreational sport activities done by urban communities, 3) the value of individual’s physical and psychosocial aspects,4) potential space for individual who do recreational sport activities. This research used ethnographic study with empirical and theoretical approaches. We conclude that the recreational sport activities as an option activity for the urban community, and is quite representative to facilitate the needs of sport cultures, and a sense of concern for the environment which useful in maintaining health.